Penegakan Hukum Oleh Penyidik Terhadap Anak Yang Berkerja Sebagai Pengemudi Truk di Wilayah Kepolisian Resor Rokan Hilir - Rizki Amin; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The need for transportation facilities needed at the first time is the human need for goods,services, and information in the process of life. The occurrence of more than one number of trafficfrom year to year that shows public awareness about the culture of orderly driving. To overcomethis problem, a lot of effort is needed - gelatin numbers and orderly. Traffic from year to year andcan generate a lot of information about traffic and traffic. So far, many students or students conducttraffic evaluations. One example is that many students who are underage by their parents drivetrucks that do not have a driver's license. In this case, the police are the party responsible for theimplementation of activities in realizing and maintaining traffic order. Like the dissatisfaction thatoccurred in the Rokan Hilir area. Therefore, it should be a problem and also needed.This type of research can be classified in this study classified in the type of sociological legalresearch. namely, research carried out by making legal identification and how the effectiveness ofthe implementation of the law applies in the community. This research was carried out in the RokanHilir Resort Police Area, because there are still many traffic violations in the Rokan Hilir area, oneof which is driving motorized trucks without having a SIM, namely children under the age of theage. Data collection techniques used in sociological legal research are interviews, questionnairesand literature review. In this study, the analysis carried out was qualitative analysis and the dataanalyzed did not use statistics or mathematics or the like. In drawing a conclusion a deductivemethod can be used, namely a way of thinking that draws a conclusion from a specific caseThe conclusion that can be obtained from the results of this study is Law Enforcement ByInvestigators Against Children Who Work As Truck Drivers in the Police Area of Rokan HilirResort through Preventive Law Enforcement and Repressive Law Enforcement. The Factors CauseChildren who work as Truck Drivers in the Police Area of Rokan Hilir Resort are to fulfill theirdaily needs, provide basic commodities and help the family's economyKeywords: Law Enforcement, Investigator, Child, Truck Driver